CURRENT STATUS OF WAITING TIME FOR CONSULTATION AND ROUTINE BLOOD TESTS AMONG OUTPATIENTS AT 103 MILITARY HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objectives: To measure waiting times for consultation, blood sampling, laboratory results, and total outpatient visit duration, and to identify factors associated with waiting time at the Military Hospital 103.Methods: A cross-sectional descriptive study was conducted on 303 outpatients at the Department of Outpatient Clinics, Military Hospital 103, from April to September 2024. Data were extracted from the hospital information system regarding timestamps of registration, consultation, sample collection, test results, and discharge. Data were analyzed using SPSS 26.0 software with descriptive statistics, group comparisons, and multivariable regression.Results: Mean waiting time for consultation was 19.0 ± 14.7 minutes; for blood sampling 16.5 ± 13.0 minutes; for hematology results 55.3 ± 25.4 minutes; and for biochemistry results 98.0 ± 24.6 minutes. The mean total outpatient duration was 234.9 ± 113.8 minutes (about 3.9 hours). Waiting times were significantly longer in the morning sessions (p < 0.001) and increased with the number of clinics visited (p < 0.001).Conclusion: Laboratory waiting time, especially for biochemical tests, represents the main bottleneck prolonging outpatient visits. Optimizing laboratory workflow and redistributing appointment schedules are necessary to shorten total visit time and enhance patient satisfaction.
Keywords: Waiting time, blood test, outpatient, Military Hospital 103, patient satisfaction.